2011
DOI: 10.1111/j.2041-1014.2011.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of oral bacteria with gingival epithelial cell multilayers

Abstract: Primary gingival epithelial cells were cultured in multilayers as a model for the study of interactions with oral bacteria associated with health and periodontal disease. Multilayers maintained at an air-liquid interface in low calcium medium displayed differentiation and cytokeratin properties characteristic of junctional epithelium. Multilayers were infected with fluorescently labeled Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum or Streptococcus gordonii, and bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
86
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 47 publications
9
86
2
1
Order By: Relevance
“…The images were manually quantified. As a positive control for the induction of apoptosis, we inoculated the oral mucosal model with F. nucleatum ATCC 10953, followed by incubation under static conditions in an anaerobic chamber for 16 h, since these conditions are known to trigger high levels of apoptotic cell death in 3-D tissue constructs (2,17). The results were expressed as the percentage of caspase-3-positive epithelial cells from the total number of epithelial nuclei quantified in the same image.…”
mentioning
confidence: 99%
“…The images were manually quantified. As a positive control for the induction of apoptosis, we inoculated the oral mucosal model with F. nucleatum ATCC 10953, followed by incubation under static conditions in an anaerobic chamber for 16 h, since these conditions are known to trigger high levels of apoptotic cell death in 3-D tissue constructs (2,17). The results were expressed as the percentage of caspase-3-positive epithelial cells from the total number of epithelial nuclei quantified in the same image.…”
mentioning
confidence: 99%
“…It has been suggested that apoptosis of epithelial cells may contribute to the loss of epithelial barrier function (6). Moreover, loss of gingival fibroblasts has been shown to be one of the largest cellular changes that occurs with periodontal disease progression and may be associated with a loss of connective tissue attachment (29,43).…”
mentioning
confidence: 99%
“…To increase relevance, a multilayer epithelial cell model has been established with which to observe P. gingivalis-host interactions (Dickinson et al, 2011). We have recently described a gingival crevice model in which primary human neutrophils can protect human gingival epithelial cells (HGEC) from P.…”
Section: Introductionmentioning
confidence: 99%